2020
DOI: 10.21608/edj.2020.79138
|View full text |Cite
|
Sign up to set email alerts
|

All on 4 Versus All on 6 implant concepts for rehabilitation of edentulous maxilla. Short term randomized clinical and radiographic study

Abstract: Purpose:The aim of the present study was to evaluate clinical and radiological outcomes of "All on 4" Versus "All on 6" implant concepts for rehabilitation of edentulous maxilla.Materials and methods: 10 patients with complete maxillary edentulism and distal extension mandibular ridges who had resorption in the posterior aspects of the maxillary ridge were randomly assigned into 2 groups: Group 1 included 5 patients who received All on four maxillary prosthesis, and group 2 included 5 patients who received All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…Hassan and Emarah (13) is contradict in their study with the present research, they reported two groups, Group 1 included 5 patients received all on four maxillary prosthesis, and group 2 included 5 patients received all on six maxillary prosthesis. The Implant stability significantly increase from base line (60) to (62) after 6 months then insignificantly increased at 12 months (63).…”
Section: Survival Ratecontrasting
confidence: 69%
“…Hassan and Emarah (13) is contradict in their study with the present research, they reported two groups, Group 1 included 5 patients received all on four maxillary prosthesis, and group 2 included 5 patients received all on six maxillary prosthesis. The Implant stability significantly increase from base line (60) to (62) after 6 months then insignificantly increased at 12 months (63).…”
Section: Survival Ratecontrasting
confidence: 69%
“…As in all-on-six cases, no cantilever is present, the risk of biomechanical complications such as prosthetic screw loosening, and implant overload is reduced. Hassan and coworkers concluded that the all-on-six implant idea is superior to the all-on-four implant concept for atrophied maxilla because it was analogous with enhanced clinical and radiological parameters in their one-year study [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…(25) .Full arch rehabilitation with five to six implants in the maxilla is becoming a common approach .Increase in the anteroposterior spread and number of implants increases the predictability of the success of all 6 implant procedures . (26) According to a systematic review, compared to the All-4 implant concept, the All-6 implant concept has a higher success rate, less plaque accumulation and pocket formation, less crestal bone loss, and increased stability after 12 months of replacement (27) . Implant techniques for these individuals have drawbacks like time-consuming procedures, blood loss, discomfort, and longer healing times.…”
Section: Discussionmentioning
confidence: 99%